Drought monitoring in the Middle East and North Africa (MENA) region: participatory engagement to inform early warning systems - Fragaszy, S. R.; Jedd, T.; Wall, N.; Knutson, C.; Belhaj Fraj, M.; Bergaoui, K.; Svoboda, M.; Hayes, M.; McDonnell, Rachael (American Meteorological Society, 2020)
When drought hits water-scarce regions, there are significant repercussions for food and water security, as well as serious issues for the stability of broader social and environmental systems. To mitigate these effects, environmental monitoring and early warning systems aimed at detecting the onset of drought conditions can facilitate timely and effective responses from government and private sector stakeholders. This study uses multistage, participatory research methods across more than 135 interviews, focus groups, and workshops to assess extant climatic, agricultural, hydrological, and drought monitoring systems; key cross-sector drought impacts; and drought monitoring needs in four countries in the Middle East and North Africa (MENA) region: Morocco, Tunisia, Lebanon, and Jordan. This extensive study of user needs for drought monitoring across the MENA region is informing and shaping the ongoing development of drought early warning systems, a composite drought indicator (CDI), and wider drought management systems in each country. Overarching themes of drought monitoring needs include technical definitions of drought for policy purposes; information-sharing regimes and data-sharing platforms; ground-truthing of remotely sensed and modeled data; improved data quality in observation networks; and two-way engagement with farmers, organizations, and end-users of drought monitoring products. This research establishes a basis for informing enhanced drought monitoring and management in the countries, and the broad stakeholder engagement can help foster the emergence of effective environmental monitoring coalitions.